2014
DOI: 10.1371/journal.pone.0108239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rabbit Annulus Fibrosus-Derived Stem Cells

Abstract: Annulus fibrosus (AF) injuries can lead to substantial deterioration of intervertebral disc (IVD) which characterizes degenerative disc disease (DDD). However, treatments for AF repair/regeneration remain challenging due to the intrinsic heterogeneity of AF tissue at cellular, biochemical, and biomechanical levels. In this study, we isolated and characterized a sub-population of cells from rabbit AF tissue which formed colonies in vitro and could self-renew. These cells showed gene expression of typical surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 43 publications
3
37
1
Order By: Relevance
“…This result is in accordance with previous in vivo studies of labeling slow cycling cells in the ISN region [21,23,24], further demonstrating the existence of stem cells in the potential ISN. Cell proliferation, as determined by the MTT assay, presented an S-shaped growth curve of both ISN-SCs and BMSCs with a logarithmic growth phase, similar to that of stem cells derived from other tissues as described in previous studies [20,29], suggesting a strong proliferation ability of ISN-SCs, though a better results was observed in BMSCs. NANOG, SOX-2, and OCT-4 are transcription factors that cooperatively maintain the regulatory system of cell self-renewal and pluripotency [42].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This result is in accordance with previous in vivo studies of labeling slow cycling cells in the ISN region [21,23,24], further demonstrating the existence of stem cells in the potential ISN. Cell proliferation, as determined by the MTT assay, presented an S-shaped growth curve of both ISN-SCs and BMSCs with a logarithmic growth phase, similar to that of stem cells derived from other tissues as described in previous studies [20,29], suggesting a strong proliferation ability of ISN-SCs, though a better results was observed in BMSCs. NANOG, SOX-2, and OCT-4 are transcription factors that cooperatively maintain the regulatory system of cell self-renewal and pluripotency [42].…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, quantitative analysis for comparing the extent of staining between induced and control groups demonstrated strong multilineage differentiation efficiencies of ISN-SCs and BMSCs. These were further confirmed by qPCR analysis, which revealed significantly increased expression of multipotential differentiation-related genes in the induced groups, including osteogenesis (Runx2, OPN, and OCN)-, chondrogenesis (SOX-9, COL2a1 and ACAN)-and adipogenesis (PPARc and C/EBPa)-related genes that were universally used in previous studies on the multilineage differentiation of stem cells [18,20]. Particularly, both of quantitative analysis for comparing the extent of staining and qPCR analysis demonstrated more powerful osteogenic and chondrogenic abilities of ISN-SCs than those of BMSCs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Spleen cells were isolated according to the method described previously [32]. Briefly, the harvested spleen tissue from the rabbits above was minced and filtrated with 70  μ m cell strainer (Corning, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…A few other studies also identified the stem cells from NP tissue and cartilage endplate, and these stem cells are comparable to bone marrow MSCs in terms of cell surface marker, differentiation capabilities. [31][32][33][34][35][36] Sakai et al 37 recently identified progenitor cells from mice and human NP cells that are Tie2 and disialoganglioside 2 (GD2) positive. The proportion of Tie2 positive cells decreased with aging and disc degeneration.…”
Section: Progenitor Cells In Intervertebral Discmentioning
confidence: 99%